2021
DOI: 10.1016/j.jbc.2021.101195
|View full text |Cite
|
Sign up to set email alerts
|

Gene body methylation safeguards ribosomal DNA transcription by preventing PHF6-mediated enrichment of repressive histone mark H4K20me3

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Enrichment analysis revealed that gene body hyper-DMGs were involved in genes related to transcription, biosynthesis, and metabolism, all of them are constitutively expressed genes. It was proposed that the function of gene body hypermethylation is most likely homeostatic, which may maintain gene expression in response to developmental and/or environmental stresses [ 38 ]. Therefore, the high gene body methylation levels in TYO fish may imply that the TYO fish was more stable than FMO fish after GCRV infection, which may be one of the reasons for age-dependent viral susceptibility in grass carp.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment analysis revealed that gene body hyper-DMGs were involved in genes related to transcription, biosynthesis, and metabolism, all of them are constitutively expressed genes. It was proposed that the function of gene body hypermethylation is most likely homeostatic, which may maintain gene expression in response to developmental and/or environmental stresses [ 38 ]. Therefore, the high gene body methylation levels in TYO fish may imply that the TYO fish was more stable than FMO fish after GCRV infection, which may be one of the reasons for age-dependent viral susceptibility in grass carp.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar to the aging male mammalian germline, the entire rDNA transcription unit in oocytes may be susceptible to aging. In contrast to promoter regions, gene body methylation promotes transcription of rDNA [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promoter methylation inhibits assembly of the transcription initiation process and, consequently rDNA transcription and expression [ 25 ]. In contrast, gene body methylation prevents binding of repressive histone marks to maintain transcription [ 26 ]. Advanced parental age is associated with increased methylation of rDNA UCE and core promoter in both oocyte and sperm, which may affect nucleolar biology of the resulting embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations